Tacrolimus-induced diabetic ketoacidosis with subsequent rapid recovery of endogenous insulin secretion after cessation of tacrolimus: A case report with review of literature. Issue 36 (September 2019) - Maruyama, Koji; Chujo, Daisuke
Abstract: Rationale: Immunosuppressive agents such as tacrolimus (TAC) and cyclosporin might cause glycemic disorders by suppressing insulin production. However, only a few cases of diabetic ketoacidosis (DKA) with longitudinal evaluation of endogenous insulin secretion related to TAC administration have been reported. Patient concerns: A 59-year-old Asian woman, who received prednisolone and TAC 4.0 mg for the treatment of anti-aminoacyl-tRNA synthetase antibody-positive interstitial pneumonia, was admitted to our hospital due to impaired consciousness and general malaise. Diagnoses: She had metabolic acidosis; her plasma glucose, fasting serum C-peptide immunoreactivity (CPR), and urinary CPR levels were 989 mg/dL (54.9 mmol/L), 0.62 ng/mL, and 13.4 μg/d, respectively. No islet-related autoantibodies were detected. Therefore, she was diagnosed with TAC-induced DKA. Intervention: Intravenous continuous insulin infusion and rapid saline infusion were administered. TAC was discontinued because of its diabetogenic potential. Outcomes: Sixteen weeks after cessation of TAC administration, she showed good glycemic control without administration of insulin or any oral hypoglycemic agents; her serum CPR level also improved dramatically. These findings suggested that TAC-induced pancreatic beta cell toxicity is reversible. Lessons: We reported a case of TAC-induced DKA with subsequent recovery of pancreatic beta cell function after cessation of TAC, resulting in good glycemic control. As TAC is widely used, we should pay attention to patients' glucose levels even though the TAC concentrations used are within the target range. Furthermore, dose reduction or cessation of TAC should be considered if hyperglycemia is detected during administration of this agent.